Peran Agen Dalam Menentukan Perencanaan Pemasaran dan Meningkatkan Minat Nasabah terhadap Produk Asuransi Syariah - Al Tasya Fitrah; Nuri Aslami (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2022)
Insurance is one of the references to meet the needs and feelings of security in the face of uncertainties that may arise in people's lives and the risks that will be experienced by the company. Insurance is one of the financial facilities (financial) of domestic life, both in the face of the risk of death and in the face of property risk. In this case, the position of the insurance agent of an insurance company is very strategic, because through this agent the company can market or sell its products to prospective consumers. Agents are also very valuable business assets. An insurance agent is a person who works alone or works in a commercial organization, represents and acts on behalf of an insurance company or sharia insurance company, who is qualified to represent the company. One of the successes of Sharia insurance companies is in the field of marketing. In addition, the agent also plays a role in carrying out activities for the community by introducing financial plans and risk management in insurance and agents also play a role in selecting risk to the customer. customer, assess and measure the extent to which risks that may arise, and determine the best approach to deal with specified risk. Marketing in Islamic insurance requires the ability to recruit, encourage, develop and sell privately (direct communication between sellers and prospective customers and arousing customer interest in the product until the customer is interested in buying the product). Keywords: Insurance, Agent, Marketing Capabilitie, Insurance Customer.